Analysis of Solid Medical Waste Management at Gunungkidul Islamic Hospital: Medical Waste Management in Hospitals - Arina Amalia; Sentot Imam Suprapto; Indasah; Inayatul Aini (Innovative Approaches in Health Science Journal, 2026)
Background: The management of solid medical waste is a crucial aspect in ensuring the safety of patients, staff, and the public, as well as in preventing environmental pollution. Purpose : This study aims To explore the implementation of temporary storage of solid medical waste at RSI Gunungkidul based on the Ministry of Environment and Forestry Regulation P.56/2015 and the Ministry of Health Decree HK.01.07/2020. Methods: The research employed a qualitative approach through in-depth interviews, observations, and document reviews, with informants from hospital management, Infection Prevention and Control Nurses (IPCN), cleaning staff, and healthcare workers. Results: The results show that solid medical waste management at RSI Gunungkidul generally complies with regulations, as indicated by the segregation of infectious, non-infectious, and sharp waste, as well as the availability of an adequate hazardous waste temporary storage facility (TPS B3). Supporting factors include the availability of facilities, personal protective equipment (PPE), a routine budget, the active role of IPCN, and collaboration with third parties. Identified obstacles include limited availability of yellow bags, restricted TPS capacity, delays in waste collection, and inconsistent placement of standard operating procedures (SOPs). Conclusion: Solid medical waste management at RSI Gunungkidul is running relatively well in accordance with standards, but still requires enhanced operational consistency and technical management for optimal performance.